El teatro de Buenos Aires en el siglo XXI: pluralismo, canon “imposible” y post-neoliberalismo - Dubatti, Jorge (Latin American Theatre Review, 2011)
With a focus on the theatre that has been produced in and exported from Buenos Aires during the first decade of the current milennium, the author proposes that the only possible canon in our globalized, heterogeneous, hybridized world is a canon imposible that recognizes and respects plurality and uniqueness. Within a macropolítica that includes the Postdictatorship and post-neoliberalism, the teatro comunitario serves as one notable example of the move in current Argentine theatre from resistance to transformation and social construction. Ricardo Bartís’s and Rafael Spregelburd’s work abroad and Daniel Veronese’s work both abroad and in commercial theatre are used to suggest esthetic and ideological changes, the effects of globalization, and the creation of an international audience for Argentine theatre. Finally, the analysis of Romina Paula’s El tiempo todo entero, Manuel Santos Iñurrieta’s Crónicas de un comediante, and Julio Molina’s Curupayty. El mapa no es un territorio—complemented by personal interviews with the dramatists and directors—confirms the ongoing shift in the theatre of Buenos Aires toward pluralism and transnationalism. (JEB, article in Spanish)